Common Beans Observatory: Monitoring open access data for the bean sector. Version Beta - Andrade, Robert Santiago; García, Carolina; García, Jeffrey; Hoyos, Nicolas; Katungi, Enid; Mwanzia, Leroy; Nyakundi, Fridah Nyabate; Rivera Vasco, Tatiana Carolina; Rubyogo, Jean-Claude; Urioste, Sergio (2022)
The Common beans observatory is an initiative led by Bioversity International and the Center for Tropical Agriculture (CIAT), with support from the Pan-African Bean Research Alliance (PABRA), to establish an information system that provides indicators related to the global bean production context. It includes data related to the bean context in each country, production system information, trade and competitiveness information, bean consumption data, inventory of technologies related to the crop, recent news, and will present data on seed systems, varieties and socioeconomics collected by PABRA in a dynamic and interactive way for the benefit of key players in the bean sector.